Referência e code-switching: traços de singularidade na linguagem de uma criança bilíngue - Bullio, Paula Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Our research is based in a dialogical approach of language acquisition, which considers that a child acquires and enters in the language through the different genres (Bakhtin, 1988, François, 1994). Thus, this work is centred in questions about personal reference, as well as the reference to the second person in both first languages of a bilingual child (French and Portuguese). In sequence, we make a parallel between the bilingual child and a monolingual child in Portuguese and the bilingual with a monolingual in French, having the same reference expressions as the aim of our analysis. This study has its basis in the studies of referential expressions proposed by Salazar-Orvig et al. (2003, 2010) and about the relation between the acquisition of personal pronoun and self-reference, it will be considered the studies of Morgenstern (2006). In Portuguese, the verbs can be used without the personal pronouns, as the verbal ending makes reference to the person. The question we stake is: The acquisition of self-reference elements and the reference to the interlocutor happens in the same way when a child is learning two languages at once? Moreover, the objective is to highlight how the interlocutors make usage of these tools in the dialog, besides the way they refer to each other. The use of these marks of reference, by the parents and by a bilingual child (Mar., 2;5-3;2), was studied in one longitudinal corpus composed by 15 sections in interactions with the parents (8 sections with the mother - who is Brazilian - and 7 with the father - who is French) in the period of almost one year. Two monolingual children were recorded in a longer period but we chose the period of one year (according to the language development in the acquisition process) and we used this data to compare with the bilingual child. All the sections covered a period of statements of two words until the adult’s syntax. The statements were analysed according to the ...

Este trabalho trata de questões de referência pessoal/auto-referência, bem como a referência à segunda pessoa, nas duas línguas maternas de uma criança bilíngue (Francês e Português). Nossa pesquisa, que se baseia em uma abordagem dialógico-discursiva de aquisição da linguagem e considera que a criança adquire e entra na linguagem por meio dos diferentes gêneros (Bakhtin, 1988, François, 1994), tem como fundamento os estudos de expressões referenciais propostos por Salazar-Orvig et al. (2003, 2010) e a relação entre a aquisição de pronomes pessoais e auto-referência, a partir dos estudos de Morgenstern (2006). Considerando-se que em Português os verbos podem ser usados sem os pronomes pessoais, pois as desinências trazem a referência à pessoa, a questão que nos colocamos é: a aquisição de elementos de auto-referência e de referência ao interlocutor acontecem da mesma maneira quando a criança está adquirindo duas línguas ao mesmo tempo? Além de responder a esta questão, pretendemos destacar como os interlocutores fazem uso destes recursos no diálogo e de que forma eles se referem um ao outro. O uso destas marcas de referência, pelos pais e pela criança, foi estudado em um corpus longitudinal composto por 15 sessões de filmagem de uma criança bilíngue (Mar., 2;5-3;2) em interação com os pais (8 sessões com a mãe - brasileira - e 7 com pai, que é francês), no período de aproximadamente um ano. As sessões cobriram o período de enunciados de duas palavras até a sintaxe adulta. Os enunciados foram analisados de acordo com a presença dos pronomes pessoais em Português e em Francês, nomes próprios e sujeito nulo. Desinências verbais, que variam em Português de acordo com o tempo verbal e a pessoa, também foram analisadas. Resumidamente, nosso objetivo foi o de explorar a especificidade do bilinguismo em relação às questões de referência. E, como resultado principal, percebemos que ...
Keywords: Linguística; Língua portuguesa; Aquisição de linguagem; Interlingua (Aprendizagem de linguas); Aquisição da segunda linguagem; Bilinguismo em crianças; Referencia (Linguistica); Bilingualism in children